Morin hydrate downregulates inflammation‐mediated nitric oxide overproduction and potentiates antioxidant mechanism against anticancer drug doxorubicin oxidative hepatorenal toxicity in rats - Ademola Famurewa; Chima Ekeleme-Egedigwe; Patience Ogbu; Ayodeji Ajibare; Moshood Folawiyo; Doris Obasi; Arunaksharan Narayanankutty (Mashhad University of Medical Sciences, 2023)
Objective: Doxorubicin (DOX) is a frontline antineoplastic drug that kills cancer cells through genotoxic mechanism; however, it induces organ toxicities. This study assayed whether morin hydrate (MOH) could abrogate DOX hepatorenal toxicity in rats.Materials and Methods: There were 4 groups of rats: Control, MOH, DOX and MOH + DOX. Rats were administered MOH (orally, 100 mg/kg bw) for 7 consecutive days, while DOX was injected (40 mg/kg, ip) on the 5th day only. Hepatorenal function markers, and glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) activities were estimated in both organs. Hepatorenal glutathione (GSH), malondialdehyde (MDA), and nitric oxide (NO) levels were estimated with histopathology.Results: DOX significantly (p<0.05) reduced antioxidant enzyme activities and GSH level, while NO and MDA levels increased (p<0.05) compared to the control. DOX prominently altered hepatorenal indices and induced histopathological alterations. MOH abrogated the DOX hepatorenal toxicity and alleviated the histological lesions in the liver and kidney.Conclusion: MOH restored the indices via antioxidant mechanism and downregulation of NO overproduction in rats.